Investigation on tribological and corrosion characteristics of oxide-coated steel and mild steel fiber-based brake friction composites. Issue 3 (21st November 2018) - S., Manoharan; R., Vijay; D., Lenin Singaravelu; Kchaou, Mohamed
Abstract : Purpose: The purpose of this work is to investigate the effect of oxide-coated steel in comparison with mild steel fibers on the tribological and corrosion performances of friction composites. Design/methodology/approach: In this study, the friction composites were developed in the form of standard brake pads by using oxide-coated steel and compared with mild steel fibers-based one without varying the other ingredients. The brake pads were developed as per the industrial procedure. The physical, mechanical, thermal properties of the developed brake pads were analyzed as per the industrial standards. The tribological properties were analyzed using the Chase test. The worn surface analysis was done using scanning electron microscope. Corrosion behavior was also analyzed in both salt and normal water conditions. Findings: The experimental results indicate that the oxide-coated steel-based friction composites brake pads possess good physical, chemical, thermal, corrosion resistance and mechanical properties with stable fade and recovery characteristics because of its oxide coating and flake morphology. Originality/value: This paper explains the influence of oxide-coated steel in friction composites for enhancing the tribological performance and corrosion resistance by its oxide coating and flake morphology which could potentially replace mild steel fibers-based problems in friction composites.